An empirical approach to develop near-field limit for radiated-emission compliance check - See, Kye Yak (2014)
Based on measurements from a near-field scanner and far-field measurements obtained in a semi-anechoic chamber, a statistical relationship is established between a magnetic field in the near field and an electric field in the far field. The relationship makes it possible to transform a radiated-emission regulatory limit from the far-field to the near-field zone. The transformed near-field limit can allow efficient prediction of radiated-emission compliance for high-speed printed circuit boards. The presented results demonstrate the feasibility of the proposed method for a quick radiated-emission precompliance check without heavy equipment investment.